Abundance and Species Composition of Cave Bats (Mammalia: Chiroptera) in Selected Key Biodiversity Areas (KBAs) of Central Visayas, Philippines - Gilbert A. Bejec; Lilibeth A. Bucol; Tomas D. Reyes; Reizl P. Jose; Agustin B. Angcog; Albert C. Pagente; Josie M. Rodriguez; Anna Lee N. Bejec; Neri Fretz P. Paglinawan (JURNAL ILMIAH SAINS, 2021)
This study assessed the abundance and species richness of bats (Order Chiroptera) inhabiting caves in three KBAs (Key Biodiversity Areas) of Central Visayas: Mt. Bandilaan in Siquijor (13 caves), Mabinay, Negros Oriental (11 caves), and Rajah Sikatuna Protected Landscape(RSPL) in Bohol (31 caves). The study was conducted between February 14 to September 20, 2019. Of the 55 caves surveyed, 35 caves were inhabited by bats. Field survey methods included mist-netting at the cave entrances and direct observations of roosting sites in each cave. This study captured 754 individuals of bats belonging to 16 species, majority of which are insectivorous species (13 species) and only three species are fruitbats (Pteropodidae). Mabinay caves had the highest number of species (11) and captured bats (271 individuals) while RSPL had 9 species (221 individuals) while Mt. Bandilaan only had five species but relatively high captured bats (262 individuals). Five species are Philippine endemics (Hipposideros obscurus, Hipposideros pygmaeus, Ptenochirus jagori, Rhinolophus inops, and R. rufus) and three Near-threatened species (H. lekaguli, M. schreibersii, and R. rufus). The rare bat species (Dobsonia chapmani) may be locally extirpated in Mabinay, where it last documented at Mambajo cave in the 1960s. The survey also noted the absence of fruit bats (observed in 2011 study) in all of the caves in Mt. Bandilaan, probably due to on-going anthropogenic activities (treasure hunting, bat hunting, guano extraction, land conversion, locals illegal entry, graffiti, etc) in caves surveyed. Large colonies of fruitbats and insect bats in RSPL may have been affected by anthropogenic activities inside the caves. Most of the caves surveyed have been promoted for ecotourism activities.Keywords: cave; chiropteran; extraction; karst; limestone